Multiple Regulations of Parasitic Protozoan Viruses: A Double-Edged Sword for Protozoa - Zhiteng Zhao; Xin Li; Nan Zhang; Jianhua Li; Na Zhao; Mengyao Gao; Xichen Zhang; Xiaocen Wang; Panpan Zhao; Lu Li; Min Sun; Lili Cao; et al. (mBio, 2023)
ABSTRACT Parasite infections affect human and animal health significantly and contribute to a major burden on the global economy. Parasitic protozoan viruses (PPVs) affect the protozoan parasites’ morphology, phenotypes, pathogenicity, and growth rates. This discovery provides an opportunity to develop a novel preventive and therapeutic strategy for parasitic protozoan diseases (PPDs). Currently, there is greater awareness regarding PPVs; however, knowledge of viruses and their associations with host diseases remains limited. Parasite-host interactions become more complex owing to PPVs; however, few studies have investigated underlying viral regulatory mechanisms in parasites. In this study, we reviewed relevant studies to identify studies that investigated PPV development and life cycles, the triangular association between viruses, parasites, and hosts, and the effects of viruses on protozoan pathogenicity. This study highlights that viruses can alter parasite biology, and viral infection of parasites may exacerbate the adverse effects of virus-containing parasites on hosts or reduce parasite virulence. PPVs should be considered in the prevention of parasitic epidemics and outbreaks, although their effects on the host and the complexity of the triangular association between PPVs, protozoans, and hosts remain unclear. IMPORTANCE PPVs-based regulation of parasitic protozoa can provide a theoretical basis and direction for PPD prevention and control, although PPVs and PPV regulatory mechanisms remain unclear. In this review, we investigated the differences between PPVs and the unique properties of each virus regarding virus discovery, structures, and life cycles, focused on the Trichomonas vaginalis virus, Giardia lamblia virus, Leishmania RNA virus, and the Cryptosporidium parvum virus 1. The triangular association between PPVs, parasitic protozoa, and hosts reveals the “double-edged sword” property of PPVs, which maintains a balance between parasitic protozoa and hosts in both positive and negative respects. These studies discuss the complexity of parasitic protozoa and their co-existence with hosts and suggest novel pathways for using PPVs as tools to gain a deeper understanding of protozoal infection and treatment.